El surgimiento de las organizaciones sociales promotoras del desarrollo local de la parroquia de Flores - Mirian Elizabeth, Quishpi Quishpi (2017)
The beginning of social organizations promoting the local development of Flores Parish, Riobamba Cantón in the province of Chimborazo, is an investigation that organizes a historical stage lived by this town. Being an eminently indigenous jurisdiction, the domination of the few mestizos that inhabit here and the injustice, discrimination and exploitation to the owners of these lands have prevailed historically, In response to this, the first ethnic organization, the Union of Flores Indigenous Organizations "UCIF", now recognized as "COCIF", emerges to fíght and claim indigenous rights and manage resources to solve the most serious problems of the communities. This actions have provoked not only some confrontations in the parish, but also several conquests for the native inhabitants of this land In addition to COCIF, there are other organizations that seek the development of Flores parish and its 27 communities. Achievements, what could not be done, differences and internal conflicts are gathered in this paper work by collecting the testimonies of the actual and historical leaders who lived these organizational processes. In addition, a historical synthesis of Flores is presented, which is very necessary for the new generations to know its origin.